2020
DOI: 10.1001/jamanetworkopen.2020.1184
|View full text |Cite
|
Sign up to set email alerts
|

Differences in White Matter Microstructure Among Children With Developmental Coordination Disorder

Abstract: IMPORTANCE Developmental coordination disorder (DCD) is a motor impairment that significantly interferes with activities of daily living. Little is known about the cause of DCD and how it develops, making it difficult to understand why children with DCD struggle in learning motor skills and to determine the best intervention to optimize function.OBJECTIVE To characterize white matter differences using diffusion tensor imaging in children with and without DCD. DESIGN, SETTING, AND PARTICIPANTS This cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 55 publications
4
27
1
Order By: Relevance
“…Thus far, diffusion MRI studies have used various analysis methods, including tract-based spatial statistics (TBSS; Williams et al, 2017 ; Brown-Lum et al, 2020 ), constrained spherical deconvolution (Hyde et al, 2019 ), tractography (Zwicker et al, 2012 ; Debrabant et al, 2016 ) and graph theory (Debrabant et al, 2016 ) to understand white matter microstructure in children with DCD. Results have shown that children with DCD have altered white matter microstructure in the corpus callosum (Langevin et al, 2014 ; Brown-Lum et al, 2020 ) and sensorimotor, corticospinal, cortico-cerebellar (Zwicker et al, 2012 ; Debrabant et al, 2016 ; Williams et al, 2017 ; Brown-Lum et al, 2020 ), and frontoparietal pathways (Langevin et al, 2014 ; Williams et al, 2017 ; Hyde et al, 2019 ; Brown-Lum et al, 2020 ). Structural connectivity between brain regions (e.g., cerebellar lobule VI and right superior parietal gyrus; Debrabant et al, 2016 ) is also implicated in children with DCD.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, diffusion MRI studies have used various analysis methods, including tract-based spatial statistics (TBSS; Williams et al, 2017 ; Brown-Lum et al, 2020 ), constrained spherical deconvolution (Hyde et al, 2019 ), tractography (Zwicker et al, 2012 ; Debrabant et al, 2016 ) and graph theory (Debrabant et al, 2016 ) to understand white matter microstructure in children with DCD. Results have shown that children with DCD have altered white matter microstructure in the corpus callosum (Langevin et al, 2014 ; Brown-Lum et al, 2020 ) and sensorimotor, corticospinal, cortico-cerebellar (Zwicker et al, 2012 ; Debrabant et al, 2016 ; Williams et al, 2017 ; Brown-Lum et al, 2020 ), and frontoparietal pathways (Langevin et al, 2014 ; Williams et al, 2017 ; Hyde et al, 2019 ; Brown-Lum et al, 2020 ). Structural connectivity between brain regions (e.g., cerebellar lobule VI and right superior parietal gyrus; Debrabant et al, 2016 ) is also implicated in children with DCD.…”
Section: Introductionmentioning
confidence: 99%
“…They used a predictive statistical model to show that the cerebellum lobule VI and the right parietal superior gyrus are the most effective for distinguishing children with DCD from children with TD. Also, a study by Brown-Lum et al (2020) which investigated the entire brain, showed a decrease in FA of the cerebral peduncle, superior cerebellar peduncle, external capsule, and splenium of the corpus callosum. In the corticospinal tract, cerebral peduncle, posterior thalamic radiation at the retrolenticular part of the internal capsule and external capsule, axial diffusivity was also reduced.…”
Section: Dti Study Resultsmentioning
confidence: 97%
“…Previous studies have also shown that children with DCD have low FA in these areas (Zwicker et al, 2012a). Brown-Lum et al (2020) found that children with DCD also had low FA in the cerebellum pathway by examining the entire brain. These pathways enter and exit the spinal cord, pons, and cerebral cortex, and cerebellum, helping to improve motor movements, learn new motor skills, and balance proprioceptive information into a posture (Keser et al, 2015).…”
Section: Discussion (Neuroimaging Studies)mentioning
confidence: 95%
“…In 2012, Zwicker et al showed that the mean diffusivity of the CST and posterior thalamic radiation was lower in children aged 8–12 years than in typically developing children without DCD [ 16 ]. In 2020, Brown-Lum et al reported that 8- to 12-year-old children with DCD had lower FA and mean diffusivity in the brain areas associated with motor and sensorimotor processing than typically developing children using tract-based spatial statistics [ 8 ]. The results of DTI studies have revealed that the microstructural abnormalities in motor function-related neural tracts could be attributed to the development of DCD.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported neural impairments in the immature brain of pediatric patients with coordination problems, the pathogenesis related to them or DCD has not been clearly demonstrated [ 5 , 6 , 7 , 8 ]. Many patients with DCD usually have no definite abnormal lesions on conventional brain magnetic resonance imaging (MRI) [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%